PENGARUH PELATIHAN KERJA APARATUR PEMERINTAH NAGARI TERHADAP PENGELOLAAN KEUANGAN NAGARI DI KABUPATEN TANAH DATAR - herlinda novita wardani (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
The purpose of this study was to analyze the effect of job training on the performance of nagari government apparatus in nagari financial management in Tanah Datar Regency. The background of this study was carried out because there was an indication of the lack of proper material and inadequate facilities received by the nagari government aapparatus in nagari financial management in Tanah Datar Regency. This study uses a quantitative approach with population of this study was all nagari government apparatus, which numbered 600 people. Sample in this study was consisted of 248 nagari government apparatus determined with Slovin formula. Besides, sample in this study was determined through Multistage Random Sampling technique. The data was collected through questionnaires using Likert scale measurement. The data was analyzed with multiple linear regression tests. The results of this study showed that the job training variable (simultaneously and partially) influenced the performance of nagari government apparatus in financial management in Tanah Datar Regency. Thus it could be concluded that job training had a significant effect on the performance of nagari government apparatus in nagari finance management in Tanah Datar Regency.